Manejo de Spodoptera frugiperda (Lepidoptera: Noctuidae) em milho pipoca, com inseticidas, volumes de calda e pontas de pulverização - Feltrin, Natalie Moraes (2022)
The popcorn maize crop is a appreciated variety in Brazil, considered of high economic value, with greater susceptibility to pests and diseases, and its main pest is the fall armyworm (Spodoptera frugiperda). This pest is a polyphagous species and its attack occurs at all stages of crop growth, which can cause limiting damage to production. The most used control is still chemical control. Among the integrated pest management (IPM) strategies, the use of biological insecticides has demonstrated efficiency, being essential for the maintenance of sustainable production with lower costs. The objectives of this dissertation were to evaluate the effectiveness of insecticide application of furrow application and seed treatment, insecticide combinations, and application technology in the control of the fall armyworm (Spodoptera frugiperda) in popcorn maize. The dissertation consists of three scientific articles. The first is entitled "Management of Spodoptera frugiperda in popcorn maize with the application of insecticides via furrow and seed treatment", which aims to evaluate the effectiveness of seed treatment and insecticide applications in furrow in the control of S. frugiperda in popcorn maize. It was concluded that the insecticides Fortenza® and Dermacor®, applied via seed treatment and Premium® via furrow, contribute to the control of S. frugiperda. The second article, entitled “Management of Spodoptera frugiperda in popcorn maize with associations of chemical and biological insecticides” aimed to evaluate the effect of different managements, combining chemical and biological insecticides, in the control of S. frugiperda, under natural infestation in corn. popcorn. It was concluded that the management with the association of chemical and biological insecticides based on Baculovirus spodoptera demonstrates effectiveness in reducing insect pest damage. In the third article, “Management of Spodoptera frugiperda in popcorn maize with the association of insecticide applications, spray volumes and spray tips”, the objective of the study was to evaluate the relationship of insecticide effectiveness, spray volumes and spray tips in the control of S. frugiperda in popcorn. The results indicate that the fan tip associated with spray volumes of 75, 100 and 150 L ha-¹ provides greater effectiveness in controlling S. frugiperda and greater productivity of popcorn maize. The number of droplet impacts per square centimeter, the coverage and deposit on the targets and the volumetric median diameter was influenced by spray nozzles and spray volumes. It was concluded that the use of insecticides via seeds or furrows, the association of chemical and biological insecticides on the shoots and the applications of insecticides with flat jet tips and volumes of 75 to 150 L ha-¹ contribute to reducing the damage caused by S. frugiperda and increase grain yield in popcorn maize.